Towards a Latin American Epistemological Freedom: The Value of Thinking Different - Concha Zelada, Renán (2021)
The present essay addresses as a starting point the value and richness of the cultural diversity of indigenous communities in the context of learning and how this knowledge is made invisible by a homogeneous curriculum that does not provide spaces to value other ways of thinking. Then, a brief historical tour is presented on the colonization of indigenous and Afro-American peoples and the effects that the rational and unquestionable thought of the European generated in it, which was characterized by exercising intellectual violence towards the knowledge of Latin American culture; to end with the cultural rescue that researchers and academics propose, through the epistemological lines of the south.